2008
DOI: 10.1007/s00192-008-0565-3
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the 24-h sensation-related bladder diary in women with urinary incontinence

Abstract: Increased bladder sensation is the most troublesome symptom of overactive bladder. In clinical practice, reliable noninvasive evaluation of bladder sensation is needed. This study was designed to determine the reliability of a 24-h sensation-related bladder diary (SR-BD) in women with urinary incontinence including clinically relevant information regarding the bladder sensation. A total of 246 women with urinary incontinence filled out a SR-BD for 3 days. They graded the perception of bladder sensation at each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 22 publications
2
26
0
1
Order By: Relevance
“…The reliability of both the urgency measure and VAS fullness measure was good to excellent, except for the voids graded as almost empty (fullness 1) and without sensation (degree of “urge 0”). These values are in agreement with the reliability measures of the “urge” scale previously published in patients with urgency, stress and mixed urinary incontinence 49. Although both scales are reliable and have a positive correlation with bladder volume, they cannot replace measuring voided volumes due to a poor agreement between either scale and the actual voided volume.…”
Section: Methods Used To Measure Sensationsupporting
confidence: 88%
See 1 more Smart Citation
“…The reliability of both the urgency measure and VAS fullness measure was good to excellent, except for the voids graded as almost empty (fullness 1) and without sensation (degree of “urge 0”). These values are in agreement with the reliability measures of the “urge” scale previously published in patients with urgency, stress and mixed urinary incontinence 49. Although both scales are reliable and have a positive correlation with bladder volume, they cannot replace measuring voided volumes due to a poor agreement between either scale and the actual voided volume.…”
Section: Methods Used To Measure Sensationsupporting
confidence: 88%
“…It has been shown repeatedly that the mean voided volumes are significantly different between different grades of desire to void and there is a positive correlation between voided volume and grade of desire to void 46–48. However, there also appears to be a large range in bladder volumes per grade of desire to void and a substantial overlap in volumes between different grades 45, 49. The relation between bladder volume and sensation is probably very complex and is unlikely to be represented by a simple linear relation.…”
Section: Methods Used To Measure Sensationmentioning
confidence: 99%
“…Urodynamic study is the standard technique used for the evaluation of bladder sensation (7,12). Moreover, the voiding diaries, which are reliable and repeatable tests, can be used for the assessment of bladder sensation (13,14). In this study, we aimed to evaluate the presence of possible differences among the urodynamic findings of MUI, UUI and SUI, and to analyze the urodynamic findings in these groups by using BSI.…”
Section: Discussionmentioning
confidence: 99%
“…One can hypothesize that such information is then stored in a sensory database like system in the brain and acts like a trigger as soon as its threshold is reached to let go a sensory warning that requires action. Studies with sensation-related voiding diaries have shown that in consecutive days, the pattern and sensation/volume relations are stable (Naoemova et al 2008). Studies on fake cystometry have also given interesting data.…”
Section: Part 2: Experiencing Sensation Related To the Urinary Bladdermentioning
confidence: 99%